Teaching Integration Tasks Based on Information Technology in Primary School Mathematics - Saidova Mohinur Jonpolatovna; Idiyeva Niginabonu Erkin kizi (Genius Journals, 2022)
This article discusses the integration of information technology, the integration of assignments, the teaching of integration tasks on the basis of information technology, its effectiveness, methods and techniques, which serve to increase information competence in the process of working in mathematics lessons in primary school.
Keywords: integration; integration tasks; information; educational effectiveness